Technical Quality of Patients with Type 2 Diabetes - jafar sadegh tabrizi; yeganeh partovi; amir bahrami; mohammad asghari (Tehran University of Medical Sciences, 2016)
Background: Type 2 diabetes is a chronic disease which has incremental prevalence regarding to unhealthy lifestyle. Based on the significant gap between received and standard care in patients with type 2 diabetes, this condition occurred high costs to health system. In order to eliminate this gap, this study aimed at measuring the technical quality of perceived care among patients with type 2 diabetes. Materials and method: A cross-sectional study was carried out among 180 people with two type of diabetes in diabetes clinic using convenience sampling method. A three part questionnaire includes demographic information, disease statue and the technical quality questions was that the validity and reliability of it was approved.  The data were analyzed using SPSS13software. Results: Total technical quality score was 2.9 which was lower than bench mark 5. The main indices related to diabetic control (HbA1c, blood pressure, LDL) were acceptable regarding Iranian diabetic guideline and they were controlled well. Conclusion: According to notable gap between existing standards and perceived care in type 2 diabetic patients, there is a good opportunity to promote quality of services.